Nursing students' and faculty members' perspectives about online learning during COVID-19 pandemic: A qualitative study - Bdair, Izzeddin A. (Teaching and learning in nursing, 2021)
During the COVID-19 pandemic and mandatory lockdown, academic institutions have shifted to distance learning. This study aims to explore the nursing students' and faculty members’ perspectives of online learning during the COVID-19 era. This qualitative study was conducted using a descriptive-phenomenology method. Data were collected in August 2020 using a purposive sampling method and telephone semi-structured interviews based on the real-life experience of nursing students and faculty members with online learning during the COVID-19. Data were transcribed verbatim and thematically analyzed using Spielberg's three-step process. Nursing students and faculty members were moderately satisfied with online learning during the COVID-19 pandemic. However, conventional learning was the preferred option. Data were classified according to the three main studied domains: advantages, challenges, and recommendations. The results revealed three themes for advantages, four themes for challenges, and four themes for recommendations. The advantages themes include a flexible learning environment, academic achievement, and student-centered learning. The challenges themes were inadequacy, academic integrity, learning environment, and family burden. The themes for recommendations were training, teaching, assessment, and quality monitoring. The current study supports the use of online learning during this lockdown. Actions to improve online learning are essential to achieve more quality education.